Immersive Pop-Up Books: Enhancing Disaster Awareness in the Merdeka Curriculum - Prastika, Bianca Ayu; Senen, Anwar; Cahya, Risky Dwi (Jurnal Prima Edukasia, 2023)
The Understanding by Design (UBD) framework is the preferred instructional model in self-directed learning. The issue addressed in this study pertains to the multitude of disasters occurring in Indonesia, thereby emphasizing the significance of acquiring comprehensive perspectives on disasters and their corresponding management strategies. It remains imperative for students to acquire a comprehensive understanding of disasters and their corresponding management strategies. The research aims to increase students' disaster literacy using the UBD learning model with pop-up book media. The research employed a quantitative methodology. The study population was students from SD N Percobaan in Padang, West Sumatra. A total of 42 students were selected as participants and were divided into two groups: a control class and an experimental class. The outcomes obtained from implementing the UBD model encompass the findings derived from rigorous statistical analysis. The test results indicate a statistically significant impact of the UBD learning model on enhancing students' disaster literacy when combined with pop-up book media. The educator's contribution has yielded practical insights, diverse perspectives, and innovative ideas that enhance the efficacy of utilizing pop-up book media to augment students' disaster literacy. The findings of this study hold significant implications for Indonesia, given its status as a nation characterized by a substantial degree of vulnerability to disasters. The intended outcome is for students to develop improved readiness to respond to disasters and better understand the necessary actions to take during emergencies.